2023
DOI: 10.1093/ecco-jcc/jjac190.0003
|View full text |Cite
|
Sign up to set email alerts
|

OP03 Highly stable epigenome-wide peripheral blood DNA methylation signatures accurately predict endoscopic response to adalimumab, vedolizumab and ustekinumab in Crohn’s disease patients: The EPIC-CD study

Abstract: Background Despite the proven efficacy of biological treatments in Crohn’s disease (CD), many patients fail to respond or lose response over time. Therefore, predictive biomarkers for treatment efficacy would be of extreme value. Previous epigenome-wide association studies associated differential DNA methylation with CD-specific phenotypes, suggesting a potential use in classification and prediction of response to treatment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…87 Distinct methylation patterns were identified in genome analysis of treatment-naïve UC patients, which identified hypermethylation of genes involved in homeostasis and defense, and hypomethylation of genes for cytokines and chemokines involved in the immune response. 89 Joustra et al 15 recently reported on three validated panels of highly stable epigenetic biomarkers that could be used to predict clinical and endoscopic response in CD patients treated with adalimumab, vedolizumab, or ustekinumab. They identified distinct CpG loci that, in combination, accurately predicted clinical and endoscopic responses.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…87 Distinct methylation patterns were identified in genome analysis of treatment-naïve UC patients, which identified hypermethylation of genes involved in homeostasis and defense, and hypomethylation of genes for cytokines and chemokines involved in the immune response. 89 Joustra et al 15 recently reported on three validated panels of highly stable epigenetic biomarkers that could be used to predict clinical and endoscopic response in CD patients treated with adalimumab, vedolizumab, or ustekinumab. They identified distinct CpG loci that, in combination, accurately predicted clinical and endoscopic responses.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Notably, for these CpG loci, methylation levels remained stable during both induction and maintenance of treatment, regardless of inflammatory status and therapeutic intervention. 15 Different mucosal methylation changes of several genes in IBD patients have been used to distinguish between CD and UC as well as differentiate from healthy controls. However, there are limitations due to differences in methylation profiles in different cell types and sites, as well as technical limitations and high cost.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Epigenetic panels are currently being evaluated for predicting treatment response to specific biologics for CD. CpG panels consisting of 100, 25 and 68 loci in peripheral blood can predict the clinical and endoscopic response to adalimumab, vedolizumab and ustekinumab, respectively, with accuracies of 73%, 88% and 94%, respectively [ 97 , 98 ]. For vedolizumab, a 23-CpG panel can predict deep remission with an accuracy of 75% [ 98 ].…”
Section: Epigenomicsmentioning
confidence: 99%
“…Patients included were obtained from the EPIC-CD study, which is a multi-center consortium with the goal of identifying prognostic biomarkers at the level of peripheral blood (PBL) DNA methylation capable of predicting response to adalimumab, infliximab, vedolizumab, and ustekinumab prior to treatment in CD patients (54). For the current study,…”
Section: Cohort Assembly and Sample Collectionmentioning
confidence: 99%
“…Blood samples were obtained from patients included in the EPIC-CD study, which is a multicenter consortium with the goal of identifying prognostic biomarkers at the level of peripheral blood (PBL) DNA methylation capable of predicting response to adalimumab, infliximab, vedolizumab, and ustekinumab prior to treatment in CD patients 19 . For the current study, 8 VDZ-treated CD patients (4 responders and 4 non-responders) were sampled for peripheral blood at a median of 26 weeks into treatment during routine care at the AmsterdamUMC hospital, location AMC, Amsterdam, Netherlands (Table 1).…”
Section: Sample Collection and Preparationmentioning
confidence: 99%